FioSchisto’s expert perspective on implementing WHO guidelines for schistosomiasis control and transmission elimination in Brazil - Menezes, Camilla Almeida; Montresor, Langia Colli; Jangola, Soraya Torres Gaze; de Mattos, Aline Carvalho; Domingues, Ana Lúcia Coutinho; Júnior, Arnaldo Maldonado; Silva, Clélia Christina Mello; Barbosa, Constança Simões; de Mendonça, Cristiane Lafetá Furtado; Massara, Cristiano Lara; Fonseca, Cristina Toscano; de Oliveira, Edward José; et al. (Frontiers in Immunology, 2023)
The World Health Organization (WHO) recognizes schistosomiasis as one of the Neglected Tropical Diseases targeted for global elimination in the 2030 Agenda of the Sustainable Development Goals. In Brazil, schistosomiasis mansoni is considered a public health problem, particularly prevalent among vulnerable populations living in areas with poor environmental and sanitary conditions. In 2022, the WHO published a Guideline encompassing recommendations to assist national programs in endemic countries in achieving morbidity control, eliminating schistosomiasis as a public health problem, and advancing towards interrupting transmission. The perspectives presented here, collectively prepared by members of the Oswaldo Cruz Foundation's (Fiocruz) Schistosomiasis Translational Program (FioSchisto), along with invited experts, examine the feasibility of the WHO recommendations for the Brazilian settings, providing appropriate recommendations for public health policies applicable to the epidemiological reality of Brazil, and suggests future research to address relevant issues. In Brazil, the provision of safe water and sanitation should be the key action to achieve schistosomiasis elimination goals. The agencies involved in measures implementation should act together with the Primary Care teams for planning, executing, monitoring, and evaluating actions in priority municipalities based on their epidemiological indicators. Host snails control should prioritize judicious ecological interventions at breeding sites. The Information, Education, and Communication (IEC) strategy should be associated with water and sanitation and other control actions, actively involving school community. To identify infected carriers, FioSchisto recommends a two-stage approach of immunological and molecular tests to verify transmission interruption during the intervention and beyond. Praziquantel administration should be done under medical supervision at the Primary Care level. MDA should be considered in exceptional settings, as a measure of initial attack strategy in locations presenting high endemicity, always integrated with water and sanitation, IEC, and snail control. To assist decision-making, as well as the monitoring and evaluation of strategic actions, there is a need for an Information System. FioSchisto considers this systematization essential to make investments in strategic research to support the improvement of schistosomiasis control actions. Efforts toward schistosomiasis elimination in Brazil will succeed with a paradigm shift from the vertical prescriptive framework to a community-centered approach involving intersectoral and interdisciplinary collaboration.